Upacara Adat Nyangku sebagai Bentuk Perayaan Maulid Nabi - Galuh Noval Firdaus; Hernawati, Riza (UNISBA Press, 2024)
Abstract. The Nyangku Traditional Ceremony is a traditional ceremony that has been carried out since tradition by the people of Panjalu that was held at the end of the month of Rabiul Awal. This traditional ceremony aims to cleanse the heirloom with the aim of honoring the struggle of Prabu Borosngora as King of Panjalu in ancient times and the first person to be considered to have converted to Islam in Panjalu land. This traditional ceremony is also a form of maulid celebration of the prophet Muhammad SAW in honor of his birth. The purpose of this study was to find out the denotative, connotative, and mythical meanings of my traditional ceremonies. The research methodology used is a qualitative method with Roland Barthes' semiotic analysis approach. The data collection used is through observation, interviews, documentation, and library studies on journals, scripts, and other sources that are considered relevant.The results of this study in each adherent ceremonial procession contain denotative, connotative, and mythical meanings. The denotative meaning is described and clearly seen from every process that goes through with the aim of cleaning the heirloom, the connotative meaning is that this traditional ceremony exists and remains as a form of tribute to Prabu Borosngora's struggle and honor the birth of the Prophet Muhammad SAW, As well as the mythical significance contained in this traditional ceremony are present based on the beliefs of the local people. Abstrak. Upacara Adat Nyangku merupakan upacara adat yang sudah dilaksanakan sejak turun temurun oleh masyarakat Panjalu yang dilaksanakan pada penghujung bulan Rabiul Awal. Upacara adat ini bertujuan untuk membersihkan benda pusaka dengan tujuan untuk menghormati perjuangan Prabu Borosngora sebagai Raja Panjalu pada zaman dahulu dan orang pertama yang dianggap memeluk agama islam di tanah Panjalu. Upacara adat ini juga sekaligus sebagai bentuk perayaan maulid nabi Muhammad SAW untuk menghormati kelahiran beliau. Tujuan dari penelitian ini ialah untuk mengetahui makna denotatif, konotatif, serta makna mitos dari upacara adat nyangku. Metologi penelitian yang digunakan ialah metode kualitatif dengan pendekatan analisis semiotika Roland Barthes. Pengumpulan data yang digunakan ialah melalui observasi, wawancara, dokumentasi, serta melakukan studi pustaka pad jurnal, skripsi, dan sumber lain yang dianggap relevan. Hasil penelitian ini dalam setiap prosesi upacara adatnya terkandung makna denotatif, konotatif, dan mitos. Makna denotatif nya tergambarkan dan terpampang jelas dari setiap proses yang dilalui dengan tujuan untuk membersihkan benda pusaka, makna konotatif nya ialah upacara adat nyangku ini ada dan tetap lestari sebagai bentuk penghormatan kepada perjuangan Prabu Borosngora dan menghormati kelahiran Rasulullah SAW, serta makna mitos yang terkandung dalam upacara adat ini hadir berdasarkan kepercayaan masyarakat setempat.